A boutique personal librarian program for transfer students. Issue 2 (12th June 2017) - Lafrance, Helene; Kealey, Shannon B.
Abstract : Purpose: The purpose of this paper is to discuss the planning, implementation and assessment of a personal librarian (PL) program for transfer students at a four-year private university. It highlights best practices to ensure the success of such a program, emphasizes the importance of collaboration with other campus units and explores the possible applications for other underserved student populations. Design/methodology/approach: This paper explains why the PL model is particularly appropriate to serve the needs of transfer students. It clearly describes the assessment methods to evaluate such a program and proposes best practices to ensure success and sustainability. Findings: Transfer students respond very positively to a PL program as shown by the number of interactions they have with their PLs and their responses to a survey. Librarians also appreciate the chance to develop meaningful relationships with students despite the addition to their workload. Practical implications: Institutions looking at ways to reach out to transfer students or other underserved populations can easily adapt the PL program described here. Originality/value: The PL concept is not new but, to the best of the authors' knowledge, it is the first time it has been applied to transfer students. The program described here is also unique because of its "boutique" approach, which emphasizes customization and personalization.